2010
DOI: 10.4103/0970-0218.74358
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, and practice of dyeing and printing workers

Abstract: Background:Millions of workers are occupationally exposed to dyes in the world, but little is known about their knowledge and attitudes toward the effects of dye on their health..Objectives:The aim of this study was to assess the fabric dyers′ and fabric printers′ knowledge, attitude, and practice toward the health hazard of dyes.Materials and Methods:The present study was taken up in the Madurai district which is situated in the Southern Tamil Nadu, India. One hundred and forty-two workers employed in small-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 4 publications
3
12
0
Order By: Relevance
“…Millions of textile workers are occupationally exposed to dyes/chemicals in the world but little is known about their knowledge towards the effects of dye/ chemicals on their health especially in the developing world, Nigeria inclusive. 17 Over 80% of the respondents in the study knew they were exposed to hazards in the workplace. This is not surprising as a good percentage of the respondents had primary school education as their lowest level of education and this could account for the high knowledge of exposure to hazards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Millions of textile workers are occupationally exposed to dyes/chemicals in the world but little is known about their knowledge towards the effects of dye/ chemicals on their health especially in the developing world, Nigeria inclusive. 17 Over 80% of the respondents in the study knew they were exposed to hazards in the workplace. This is not surprising as a good percentage of the respondents had primary school education as their lowest level of education and this could account for the high knowledge of exposure to hazards.…”
Section: Discussionmentioning
confidence: 99%
“…A semi-structured interviewer-administered questionnaire was used to assess the knowledge, attitude and safety practices of workers. The questions were adapted from previously validated tools with some modifications 5 , 6 , 12-16 and was translated to Hausa (the local language in the communities) and back translated to English by two different scholars. The questionnaire was administered to the textile dye workers in Hausa language by the research assistants who were trained on the objectives of the study, data tools and interpersonal communication.…”
Section: Methodsmentioning
confidence: 99%
“…This might be due to the low awareness among the workers about the adverse health effects of noise. Other researchers found that half of the workers had positive attitude towards using PPEs and only 34% of them were using theirs during work (Paramasivam et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…In a study in India (Paramasivam et al, 2010), 73% of the workers had been instructed on safe methods of handling dyes. This discrepancy might be due to the fact that those workers were specifically dealing with chemicals, while our study subjects as students deal with multiple exposures and are not yet specified.…”
Section: Discussionmentioning
confidence: 99%
“…All the workers believed that safe methods of handling dyes were important, however; it was also found that only 34% of these workers used personal protective equipment (PPE) as gloves while working. 7 In another study carried out by Yu et al, 2005 about the knowledge, attitude and practice of printing workers towards organic solvents in Hong Kong, it was found that these parameters were generally low where good knowledge was positively related to being aware of legislations while appropriate attitude was associated with good knowledge and younger age. Safe practice was neither related to knowledge nor attitude but was associated positively with being informed about safety precautions and information from supervisors.…”
Section: Introductionmentioning
confidence: 96%